“Female Preponderance” of Depression in Non-clinical Populations: A Meta-Analytic Study - Wang, Kui; Lu, Han; Cheung, Eric F. C.; Neumann, David L.; Shum, David H. K.; Chan, Raymond C. K. (Frontiers in Psychology, 2016)
Clinical observations and research suggest a female preponderance in major depressive disorder (MDD). However, it is unclear whether a similar gender difference is found for the reporting of depressive symptoms in non-clinical populations. The present meta-analysis was conducted to address this issue. We searched for published papers targeting non-clinical populations in which the 21-item Beck Depression Inventory (BDI) was used. Eighty-four papers (91 studies) published between 1977 and 2014 were included in the final meta-analysis, which comprised 23,579 males and 29,470 females. Females in the general population reported higher level of depressive symptoms than males (d = -0.187, corresponding to 1.159 points in the 21-item BDI). This pattern was not found to influence by years of publication, socioeconomic status or version of the BDI used. Using age group as a moderator, studies with adolescents and young adults were found to show a smaller effect size than studies with older participants. Our results appear to confirm the “female preponderance” in the level of self-report depressive symptoms in the general population, and support the social gender role theory in explaining gender difference over biological susceptibility theory and evolutionary theory.